Pendampingan Teknis dan Pembinaan Petani dalam Peningkatan Kesadaran Lingkungan dan Kemandirian Pertanian Berkelanjutan di Kelurahan Lirboyo, Kediri - Yuliyanto, Yuliyanto; Chamro', Wardatul; Hadiyanti, Nugraheni; Junaidi, Junaidi; Kustiani, Edy; Muharram, Muhammad; Sidhi, Eko Yuliarsha (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2025)
The technical assistance and farmer empowerment activities in Lirboyo Subdistrict aim to raise environmental awareness, reduce dependency on chemical inputs, promote self-reliance in sustainable agricultural practices, and engage in the Go Green campaign. This program involves collaboration between university students, local farmers, and vocational high school students (SMKN), who work together through various activities. A Participatory Rural Appraisal (PRA) approach, along with preliminary observations and Focus Group Discussions (FGDs) involving local farmers, students, and participants from SMKN 1 Kediri City, was employed to identify needs. Furthermore, the program used demonstration methods to provide skills in the production of organic fertilizers, engaging farmers, university students, and vocational students in the process. The outcomes of this program show highly positive impacts. These include increased knowledge and skills among farmers, students, and vocational students in producing and applying liquid bokashi fertilizer, implementing natural pest control, and a shift in attitudes as indicated by participants’ growing awareness of the importance of environmental preservation. Participants also expressed a willingness to share information about organic fertilizer production with friends, family, and the surrounding community through direct communication and social media videos. Additionally, participants expressed interest in maintaining ongoing discussions with agricultural extension officers through digital messaging platforms. Kegiatan pendampingan teknis dan pembinaan petani di Kelurahan Lirboyo bertujuan untuk meningkatkan kesadaran lingkungan, mengurangi ketergantungan penggunaan bahan kimia, mendorong kemandirian dalam praktik pertanian berkelanjutan dan terlibat dalam upaya kampanye go green. Program ini melibatkan mahasiswa, petani, dan siswa SMKN, yang bekerja sama dalam berbagai kegiatan. Pendekatan yang dilakukan untuk mengidentfikasi kebutuhan adalah dengan pendekatan PRA (Particaptory action research), observasi pendahuluan, FGD yang melibatkan petani setempat, mahasiswa, dan siswa SMKN 1 Kota Kediri. Selanjutnya, kegiatan ini juga mengguanakan metode Demonstrasi untuk memberikan keterampilan pembuatan pupuk organik yang melibatkan petani, mahasiswa dan siswa SMKN 1 Kediri. Hasil dari program ini menunjukkan dampak yang sangat positif. Hasil dari kegiatan ini dapat terlihat dari peningkatan pengetahuan dan keterampilan petani, mahasiswa, dan siswa SMK berupa kemampuan dalam membuat dan mengaplikasikan pupuk bokhasi cair, mampu melaksanakan pengendalian OPT alami, serta berdasarkan hasil komunikasi dengan peserta kegiatan ingin terjadi perubahan sikap berupa kesadaran pentingnya menjaga kelestarian alam dan berkeinginan untuk ikut menyebarkan informasi terkait pembuatan pupuk organik kepada teman, keluarga, dan masyarakat disekitarnya melalaui komunikasi langsung, dan video di sosial media. Selain itu, para peserta juga ingin untuk dapat berdiskusi secara berkelanjutan melalui pesan digital dengan penyuluh.